Analisa Hambatan Samping dan Manajemen Lalulintas Ruas Jalan - Jansen, Freddy; Sendow, Theo K. (Sam Ratulangi University, 2017)
Manado City is the capital of North Sulawesi province which is the center of economic activities, education, and even other activities. As one of the developing cities in Indonesia, the continuous urban development had leads to increased inflows of vehicles, goods, and even people. These were results in arising of some traffic problems such as increased of existing traffic volume. In order to overcome this it is necessary that planned and directed traffic management so that the solution at one point will not cause problems at another point.For planned and targeted traffic management, it is necessary to know the behavior of traffic characteristics such as volume, speed and density. By knowing the volume and speed it can be known how much capacity of the road segment. Side constraints that occur on the roadway greatly affect the level of service on the road, the effect is very clearly visible is the reduced vehicle speed, so indirectly the side barriers that occur affect the reduced capacity and road performance.The long-term goal of this research is to address the problems that occur such as traffic congestion due to increased traffic volume while for specific targets is to provide a formulation for planners, implementers of the world of road traffic management applications and to the world of academics on how to analyze traffic management and defense strategies Required road performance in Manado City. To overcome the problem, it is necessary to analyze the effect of accurate side barriers in order to carry out good traffic management. Analysis of side obstacle factors can be used as an evaluation material for adjustment factor side barrier at the study location.The effect of side barriers was analyzed using a comparison between the capacities at high side resistance and at low side barriers.This capacity is obtained through the linear Greenshields, logarithmic Greenberg, and exponential Underwood models, which are then compared to capacity using the MKJI 1997 method. Capacity using Greenshields, Greenberg, and Underwood modeling was obtained by first finding the mathematical relationship between the highest Volume-Speed-Density parameter and the coefficient of determination (R2). The expected output of research is in the form of technology product in the form of traffic management and strategy of maintaining the required road performance in Manado City which can be directly utilized by society, government, industry, university. Publications, textbooks, models, social engineering on Capacity and Road Traffic Management Road-based roads.Keywords: side constraint, road capacity.